The Cyber-front in the War on Terrorism: Curbing Terrorist Use of the Internet - Hinnen, Todd (Science and Technology Law Review, 2004)
As an affordable, anonymous, secure, geographically unbounded, and largely unregulated medium for commerce and communication, the Internet provides users with an unprecedented global marketplace in which to conduct financial transactions and exchange ideas. These same characteristics, however, render the Internet an inviting environment for vast fraud schemes, money laundering, and communication among criminal coconspirators. It has become increasingly clear that terrorist organizations avail themselves of the opportunities afforded by the Internet to recruit and train adherents and foot soldiers, to raise and move funds, and to plan and execute attacks. This Article explores law enforcement’s ability to combat terrorist organizations’ use of the Internet to raise and move funds, communicate, and orchestrate acts of terror. First, the Article examines the online mechanisms through which terrorist organizations raise funds online, citing examples in which terrorists have raised money by soliciting funds directly over the Internet, exploiting facially-legitimate online charities, or garnering the proceeds of Internet crimes. Second, the Article explores the online commercial applications through which terrorist organizations transfer resources from these fund-raising sources to their operational corps. Third, the Article investigates the online means by which terrorist organizations communicate to recruit and indoctrinate supporters, to orchestrate fund-raising and disbursement efforts, and to devise and implement violent operations. With regard to each of these topics, the Article discusses the challenges posed to the United States government’s efforts to prevent, investigate, and prosecute such conduct under United States law.